MENINGKATKAN KEMAMPUAN GURU DALAM MANAJEMENKELAS MELALUI SUPERVISI KLINIS DI MTS AZZAINIYYAH - Kurniawan, Rizki; Ginanjar, Wahyu (Epistemic: Jurnal Ilmiah Pendidikan, 2023)
This study is motivated by the low classroom management skills among teachers at MTs Azzainiyyah Sukabumi West Java, where classroom management is often viewed as a mere routine without optimal efforts to create a conducive learning environment. The primary objective of this research is to enhance teachers' classroom management skills through a structured clinical supervision approach. The research employs a School Action Research (SAR) method with a qualitative approach. The research design involves two cycles consisting of observation, reflection, and corrective actions on the teachers' teaching practices in the classroom. Data were collected through observation, interviews, and documentation, and analyzed using a qualitative analysis model. The results indicate a significant improvement in classroom management skills, from 65% in the first cycle to 80% in the second cycle. This improvement includes better emotional management of students, more effective time management, and improved control of student behavior. The implications of this study suggest that clinical supervision can be an effective tool in enhancing teachers' skills in creating a more positive and productive learning environment, particularly in Islamic-based educational settings. This research also contributes to the development of clinical supervision models in Islamic education.